CICLO DE VIDA Y FORMAS JUVENILES DE EURYMETOPUM MULTINOTATUM PIC, 1950 (COLEOPTERA: CLERIDAE: PHYLLOBAENINAE) (Acta Entomológica Chilena, 2022)
The life cycle of Eurymetopum multinotatum Pie, 1950 (Coleóptera, Cleridae), under laboratoryconditions, is studied in this paper. The stock examples were collected from the Reserva NacionalRío Clarillo, Región Metropolitana de Santiago, trying to secure fertilized females. The ovipositionalcharacteristics of the species, the duration and permanence of the different stages, i.e., immaturesand adults, and natural mortality and survival of them, are recognized. All these stages are describedand illustrated.